Treatment of palm oil mill effluent using hybrid aerobic submerged membrane bioreactor - Mohammed, Abdulsalam (2020)
Palm oil mill effluent (POME) is considered high strength wastewater owing to the excessive concentration of organic and inorganic contaminants. The presence of colour pigments (such as lignin, melanoidin and tannin) poses a considerable hazard to the environment and this is because of their carcinogenic nature. Though, the popular conventional biological treatment approach has been reported effectual for remediating biodegradable contaminants but often failed to reduce the recalcitrant colour pigments, and as such they were unable to reduce the concentration to acceptable limits (100 and 200 ADMI class A and B, respectively) of the Department of Environmental (DOE), Malaysia. This was due to the predominant complex aromatic ring structures of the colourants which are difficult to break biologically. In this regards, the objective of this study mainly focused on developing a novel hybrid of aerobic system and physical techniques which constitutes the combination of plastic-bio sorbent (PBS) and nanocomposite membrane for remediating the colour content and other contaminants present in POME. Initially, a novel start-up approach was applied to the aerobic section of the hybrid system by subjecting the sludge-seed to a culture period of 10 days to build-up the active-biomass. The aerobic activated sludge section (AASS) was inoculated with 6 L of mixed sludges along with 1 L of dairy wastewater and 10 g of yeast extract to stimulate biomass build-up under steady aeration of 3 Lmin-1. The remediation efficiency after acclimation was evaluated based on Randomized Multi-Level Categoric Design at a loading rate of 0.895 g CODL-1d-1, HRT of 6 to 36 h and aeration intensity of 3 to 5 Lmin-1. The aerobically treated POME was further polished using customised plastic bio-sorbent (PBS) Cosmo balls. The PBS was prepared by coating an optimal dosage of microwaved irradiated coconut shell activated on the Cosmo balls and a total of 161 balls were incorporated to remove the colourants, as well as COD, TSS and turbidity by adsorption from the aerobically treated POME. In order to further polish the treated POME, a special nanocomposite membrane was formulated, characterized and applied under continues flow conditions. The membrane formulations contain varied Nano-MgO (NMO) loading (0, 0.25, 0.50, 0.75 and 1.25 g) and the resulted dopes were spun distinctly using phase inversion technique. The resultant hollow fibres were characterized to identify the best performing sample-based on structural morphology, porosity, hydrophilicity, elemental compositions, surface zeta potential, and thermal stability. Noticeably, the permeability flux, fouling resistance and colour rejection improved with the increase in NMO loading. PVDF-PEG with 0.50 g-NMO loading demonstrated an exceptional performance with 198.35 L/m2-h and 61.33 L/m2-h of clean-water and POME permeability flux, respectively. More so, it had an upturn antifouling performance with a steady flux recovery, reversible fouling percentage and irreversible fouling percentage of 90.98, 61.39 and 7.68 %, respectively, and these results remains relatively steady even after 3 cycles of continuous filtrations for a total period of 9 hours. Based on this, PVDF-PEG with 0.50 g-NMO loading was selected and applied for the final polishing of the pre-treated POME. The result of the treatment processes indicated that the novel start-up approach of this study significantly shortens the acclimatization period to 31 days due to the dense active-biomass concentration (17266~23362.45 mg/L). The colour, chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS) and turbidity removal efficiency after acclimation at 30-36h HRT and 4~5 Lmin-1 were 63.45, 94.30, 98.11, 98.95 and 96.68 %, respectively. Statistically, the HRT shows exceptional influences on the overall performance with synergistic R2 of 0.9740. The PBS improves the quality of the aerobically treated POME at the optimal dosage of 3.289 g per 100 mL sample size to a magnitude of 95.72, 99.09, 100, 75.29 and 98.31 % for COD, BOD, TSS, colour and turbidity after contact periods of 3-5 h, respectively. The PVDF-PEG membrane with 0.50 g-NMO loading was able to reduce the colour concentration of the aerobically-PBS pre-treated POME to an acceptable discharge limit of 145-170 ADMI, with good resistance to fouling. At sub-critical flux of critical flux of 21 L/m2-h, the TMP fluctuate weakly between 10~11 psi, and 14 psi after a repeated application for 25 days’ filtrations. Besides, the varied aeration intensity demonstrated a significant effect on the consistency of the permeate. The modified membrane shows a consistent permeate at 5 L/min of scouring aeration with less than 2 L/m2-h declination in the permeability flux. At the end of each filtration experiment, the physicochemical qualities of the permeate based on COD, TSS, BOD and turbidity concentrations were 36.14 mg/L, 0 mg/L, 0 mg/L and 8 FAU, respectively. Conclusively, the remediation performance exceeds 98 % and with compliance to the discharge standard Class-A except for the colour which managed to certify the Class-B standard. It can be deduced that the successfully developed and evaluated novel hybrid treatment system was able to reduce the colour concentration to comply with the discharge limits of the department of environment (Class-B ≤ 200 ADMI), and also all other contaminants such COD, TSS, BOD and turbidity were reduced far below the standard limit Class-A. The incorporated NMO at 0.50 g loading improved the antifouling and colour rejection properties of the modified nanocomposite PVDF-PEG membrane. Thus, the implication of these studies demonstrated a full capacity of deterring all possible adverse effect of the colourants alongside with other contaminants on the environments. Therefore, implementation of this hybrid system will assist the industries to comply with the stringent discharge limits completely.